ISOLASI DAN SKRINING JAMUR PELAPUK PUTIH DARI MATERIAL LIGNOSELULOSA DI EDUPARK UNIVERSITAS MUHAMMADIYAH SURAKARTA - Hafiyan, Zahroh Al Wahid, Triastuti Rahayu, S.Si, M.Si (2017)
Edupark Universitas Muhammadiyah Surakarta (UMS) is the ideal place to growth the fungi with an average temperature of 25°C-31°C. Edupark is dominated by lignoselulosa trees that allows timber wood fungi growth, especially white rot fungi. This research aims to find out the result of the isolation and screening of white rot fungi contained in Edupark UMS. This research uses purposive random sampling method namely explorative. The sampling was done on a wood rot fungi in the living and dead wood. Wood rot fungi isolates were subcultured on media Bavendamm for screening of white rot fungi. The result shows that from 28 isolates of the fungi, there are 17 isolates (61%) positive (+) is a mushroom of white rot, 6 isolates (21%) negative (-) excluding mushrooms of white rot, and 5 isolates (18%) were not tested because it isolates did not live or contaminated.